The Future of Radioactive Waste Governance Lessons from Europe - Arentsen, Maarten; van Est, Rinie (Energiepolitik und Klimaschutz. Energy Policy and Climate Protection, 2023)
This Open Access book examines the radioactive waste management policies of ten European countries: Belgium, Finland, France, Germany, Italy, the Netherlands, Spain, Sweden, Switzerland and the United Kingdom. Most countries are in the process of planning and creating final storage solutions, while none has yet finalized this process. Over the past decades many countries have been renewing their decision-making processes and the institutions that support them. The book provides 16 lessons that may advance the future democratic decision-making process around radioactive waste management. The Editors Maarten J Arentsen is associate professor emeritus of Energy Innovation at the University of Twente in the Netherlands. Rinie van Est is research coordinator at the Rathenau Instituut and professor of Technology Assessment and Governance at Eindhoven University of Technology (School of Innovation Sciences).